ANALISIS DETERMINAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KAWASAN URBAN TANGERANG: PENDEKATAN MULTIDIMENSI - Benyamen Minggus Melatnebar (Accounting Journal of Ibrahimy (AJI), 2026)
State revenue optimization from the domestic sector relies heavily on the degree of tax compliance. This research is oriented to examine and construct the significance of the influence of taxpayer awareness, level of tax knowledge, and the service quality provided by fiscal apparatuses on Individual Taxpayer (WPOP) compliance at Tax Service Offices (KPP) in the Tangerang region, Banten. Through a quantitative research design, structured questionnaires were distributed to 120 participants selected using a purposive sampling technique. The processing of empirical databases was resolved via multiple linear regression estimation based on SPSS version 26. Statistical output proves conclusively that taxpayer awareness, understanding of tax rules, and the operational quality of the fiscal authority have a significant effect on WPOP compliance, both partially and simultaneously. Among the variable interactions tested, the quality of fiscal service recorded the most dominant magnitude of influence. These findings reinforce the necessity of tax bureaucratic reform oriented toward service modernization and interactive education to stimulate voluntary tax compliance in urban clusters.